MODEL KEBUTUHAN ANGKUTAN UMUM KHUSUS PEREMPUAN (STUDI KASUS : ANGKUTAN UMUM DI KOTA BATAM, KEP. RIAU) - Wahyuni, Atik; Sulistio, Harnen; Wicaksono, Achmad; Djakfar, Ludfi (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Many obtacles and problem for woman if use public transportation, including cost, policy, convenience and most important is the increasingly widespread violence on women in public spaces or public transportation, so it is necessary to conduct a study on public transportation for women. The objectives of this study is to obtain public transport modal choice model of women's. The method use in this study to conduct a survey respondent female passenger on social economic characteristics, trip characteristics and stated preference. The results from this research  is the selection of a model mode public transportation for women UAUP – UAU = 0,328 + 0,150 ∆X5